2004
DOI: 10.1111/j.1365-2249.2004.02593.x
|View full text |Cite
|
Sign up to set email alerts
|

A mycobacterial lipoarabinomannan specific monoclonal antibody and its F(ab′)2 fragment prolong survival of mice infected withMycobacterium tuberculosis

Abstract: SUMMARYLipoarabinomannan (LAM) is a major structural carbohydrate antigen of the outer surface of Mycobacterium tuberculosis . High antibody titres against LAM are often seen in active tuberculosis (TB). The role of such LAM-specific antibodies in the immune response against TB is unknown. Here we have investigated a monoclonal antibody (MoAb) SMITB14 of IgG1 subclass and its corresponding F(ab ¢ ) 2 fragment directed against LAM from M. tuberculosis strain H37Rv. MoAb SMITB14 was shown by immunofluorescence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
140
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(150 citation statements)
references
References 38 publications
(33 reference statements)
4
140
0
1
Order By: Relevance
“…However, we and others have shown in previous studies that passive transfer of monoclonal antibodies can reduce infection with MTB in mice [9,[22][23][24][25][26][27][28], although it is unclear if active immunisation could induce similar levels of antibodies and of the same epitope specificity. Therefore, further work is required to fully characterise the role of Ab responses induced by the Nano-AH vaccine, in protection against MTB infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, we and others have shown in previous studies that passive transfer of monoclonal antibodies can reduce infection with MTB in mice [9,[22][23][24][25][26][27][28], although it is unclear if active immunisation could induce similar levels of antibodies and of the same epitope specificity. Therefore, further work is required to fully characterise the role of Ab responses induced by the Nano-AH vaccine, in protection against MTB infection.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies regarding the role of humoral immunity in the containment of M. tuberculosis or the development of tissue damage vary from study to study [14][15][16]. These discrepancies are probably due to the fact that different models and parameters of mAbs were used in these different studies for assessing the outcome of infection [17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as an intracellular pathogen, it has been argued that Mtb would not be within the therapeutic reach of antibodies. Nonetheless, multiple studies have shown the efficacy of mAbs in ameliorating murine models of TB infection (6)(7)(8)(9)(10)(11)(12), and antibodymediated immunity to several intracellular pathogens, including Cryptococcus neoformans and typhoid Salmonella, has been documented (13), raising the possibility that antibody-mediated immunity may also exist for TB. Pooled Igs from human donors have been shown to protect mice against Mtb (14), but it was not known if this was caused by a generalized immunomodulatory effect (15) targeting the inflammatory component of the disease or whether protective antibodies directly targeting critical mycobacterial antigens could be isolated from individuals.…”
mentioning
confidence: 99%